Analisis Rasio Profitabilitas dan Rasio Aktivitas dalam Mengukur Kinerja Keuangan - Zulkifli , Zulkifli; Machmud, Mulyana; Lukman, Siti Diva Syarifah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
This research aims to find out how the financial performance of PDAM Tirta Nene Mallomo Sidrap district is measured using Profitability Ratios and Activity Ratios. The analytical method used in this research is the financial ratio analysis method. The financial reports are then analyzed using profitability ratios (Net Profit Margin, Return on investment, and Return on Equity) and Activity ratios (Inventory Turn Over, Working Capital Turn Over, Fixed Assets Turn Over, and Total Assets Turn Over).These results show that: for the profitability ratio, namely Net Profit Margin, from 2020 to 2022 it does not comply with established industry standards. Return on investment, from 2020 to 2022, does not yet comply with established industry standards, and Return on Equity, from 2020 to 2022 does not comply with established industry standards. For the Activity ratio, namely Inventory Trun Over, from 2020 to 2022 it is in accordance with established industry standards. For Working Capital Turn Over, 2020 to 2022 does not yet meet established industry standards. For Fixed Assets Turn Over, 2020 to 2022 does not yet comply with established industry standards and Total Assets Turn Over, 2020 to 2022 does not comply with established industry standards.